Spontaneous rupture of the esophagus - Suiffet, Walter (Cirugía del Uruguay, 1975)
The subject thoroughly discussed. Terminology is studicrl, f1nd lhe one expressed in the Utle is nc('~pted. Its patology shows that the most írequent site of lesion is the lower third, left posterolatcrnl íaee ol the esophagus. Les!'l-frequent lesions are described. The severe c.onsequeI'.ces are rnediastinitis and hydropneurnothorax. lt is seen in the mole sex, among good caten and ~tmlt people. Vorniting produces a sudden inerease in the-pressure and it leads to rupture. Topography i5 explained by the characteristics oí the low portion oí the esopbagus and by the aclion o[ hypcrpressure. It ha¡:¡ bceo experimentally reproduced. Rupture -produces s~vere clinIcal pietures, with shock ;¡nd thoracle and cervical manlfestCltionS. Diagnosis must be made through th e cliníenl picture and radíography. Treatment must be surgical, under any condition lhat lhe patlent be. Thorncotomy and closing oí the perforation is the adequate therapy. The prognosis is bad because. oí the diagnostlc difficultics and the sc" crily of the lesiono